The diversity weighted Living Planet Index: controlling for taxonomic bias in a global biodiversity indicator - McRae,Louise; Deinet,Stefanie; Freeman,Robin (PeerJ Preprints, 2016)
As threats to species continue to increase, precise and unbiased measures of the impact these 14 pressures are having on global biodiversity are urgently needed. Some existing indicators of the 15 status and trends of biodiversity largely rely on publicly available data from the scientific and grey 16 literature, and are therefore prone to biases introduced through over-representation of well-studied 17 groups and regions in monitoring schemes. This can give misleading estimates of biodiversity trends. 18 Here, we report on an approach to tackle taxonomic and geographic bias in one such indicator 19 (Living Planet Index) by accounting for the estimated number of species within biogeographical 20 realms, and the relative diversity of species within them. Based on a proportionally weighted index, 21 we estimate a global population decline in vertebrate species between 1970 and 2012 of 58% rather 22 than 20% from an index with no proportional weighting. From this data set, comprising 14,152 23 populations of 3,706 species from 3,095 data sources, we also find that freshwater populations have 24 declined by 81%, marine populations by 36%, and terrestrial populations by 38% when using 25 proportional weighting (compared to trends of -46%, +12% and +15% respectively). These results not 26 only show starker declines than previously estimated, but suggests that those species for which 27 there is poorer data coverage may be declining more rapidly.
Keywords: biodiversity indicators; biodiversity; ecology; zoology